St. Kitts and Nevis : 2011 Article IV Consultation and Request for Stand-By Arrangement: Staff Report; Staff Supplements; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for St. Kitts and Nevis. (IMF Staff Country Reports; Country Report ;, 2011)
Following a two-year long recession, a gradual recovery of St. Kitts and Nevis' highly indebted economy is under way. The government has shown remarkable resolve in pursuing fiscal consolidation. Notwithstanding the fiscal adjustment, a comprehensive and timely public debt restructuring is critical for the program to be fully financed and to achieve debt sustainability. Available financial sector indicators point to a well-capitalized banking system. Regulation of the non-bank financial sector has been strengthened, but continued efforts are needed to ensure effective supervision.